2019
DOI: 10.1039/c9ra05810a
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chromium(vi) from polluted wastewater by chemical modification of silica gel with 4-acetyl-3-hydroxyaniline

Abstract: Use of a newly synthesized Si-CPTS-AHAP adsorbent in the removal of Cr(vi) ions in wastewater treatment systems may potentially lead to low cost and highly efficient heavy metal removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 86 publications
2
24
0
1
Order By: Relevance
“…In the composite (Figure c), the peaks of ASG and Pani match well with the previously reported results. , The main characteristic peak at 950 cm –1 is attributed to the silanol groups (Si–O–H) of the ASG . Additionally, the bands of ASG at 1058 and 795 cm –1 are assignable to asymmetric and symmetric of the siloxane group (Si–O–Si), and 3465 cm –1 corresponds to the stretching vibration of the hydroxyl (−OH) group . In the case of Pani, characteristic IR bands at both 3027 and 2968 cm –1 corresponded to aromatic C–H stretching, , while peaks at 1560 and 1479.9 cm –1 arise due to CC stretching of the quinonoid and benzenoid rings, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the composite (Figure c), the peaks of ASG and Pani match well with the previously reported results. , The main characteristic peak at 950 cm –1 is attributed to the silanol groups (Si–O–H) of the ASG . Additionally, the bands of ASG at 1058 and 795 cm –1 are assignable to asymmetric and symmetric of the siloxane group (Si–O–Si), and 3465 cm –1 corresponds to the stretching vibration of the hydroxyl (−OH) group . In the case of Pani, characteristic IR bands at both 3027 and 2968 cm –1 corresponded to aromatic C–H stretching, , while peaks at 1560 and 1479.9 cm –1 arise due to CC stretching of the quinonoid and benzenoid rings, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the adverse effects of these pollutants on the ecosystem, several methods have been employed to sequestrate these pollutants from polluted water, such as advanced oxidation process (AOP), coagulation, reverse osmosis, ion-exchange, membrane, and chemical precipitation. ,, However, these water purification methods suffer from high energy utilization, evolution of secondary pollutants, high cost, more processing time, and poor sequestration of targeted pollutants . Among these techniques, the adsorption method performs a high level of efficacy in the removal of contaminants at a relatively low cost without releasing byproduct pollutants .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGA curves indicate the occurrence of two-steps mass losses for Cs, Cs–Si, and Cs–Si–Hap ( Figure 4 a). The first-step, in the temperature range of 45–100 °C, was due to the removal of adsorbed water (dehydration) molecules [ 23 ]. The second mass loss was observed in the range of 200 to 400 °C, which was due to the decomposition of volatile organic matter for Cs and the thermal decomposition of the inorganic compound present in Cs–Si and Cs–Si–Hap composite [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown the effectiveness of materials modification by Si gel for Cr ions adsorption. The presence of hydroxyl and silanol groups on the Si gel surface enhanced its affinity towards Cr ions adsorption [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%